Glasgow Coma Scale (GCS) dan Tekanan Darah Sistolik Sebagai Prediktor Outcome Pasien Cedera Kepala: Glasgow Coma Scale and Systolic Blood Pressure As Outcome Predictors For Head Injury Patients - Marbun, Agnes Silvina; Sinuraya, Elida; Amila, Amila; Simanjuntak, Galvani Volta (Bali Medika Jurnal, 2020)
Because of the relatively high mortality rate in head injury patients requires an accurate initial assessment to predict the outcome and appropriate nursing interventions in accordance with patient’s condition. This study examined Glasgow Coma Scale (GCS), systolic blood pressure, and respiratory rate as mortality predictors in patients with head injury at Haji Adam Malik Central Hospital in Medan. It was an analytical observational study with retrospective approach. The research population was medical record of head injury patients in the period of January – December 2018 in Haji Adam Malik Central Hospital. The sampling was taken by purposive sampling technique with several criteria including: having a GCS score, systolic blood pressure, respiratory rate at the time the patients admitted to the emergency room and was not a transferred patient. The results of logistic regression analysis showed that there was a correlation between GCS score (p 0.000; OR 3.299) and systolic blood pressure (p 0.024; OR 1,044) toward mortality of head injury patients. It is concluded that GCS and systolic blood pressure statistically increase the prediction of mortality in patients with head injury.